Culturally Safe Health Initiatives for Indigenous Peoples in Canada: A Scoping Review. Issue 4 (December 2018) - Brooks-Cleator, Lauren; Phillipps, Breanna; Giles, Audrey
Background: Cultural safety has the potential to improve the health disparities between Indigenous and non-Indigenous Canadians, yet practical applications of the concept are lacking in the literature. Purpose: This study aims to identify the key components of culturally safe health initiatives for the Indigenous population of Canada to refine its application in health-care settings. Methods: We conducted a scoping review of the literature pertaining to culturally safe health promotion programs, initiatives, services, or care for the Indigenous population in Canada. Our initial search yielded 501 publications, but after full review of 44 publications, 30 were included in the review. After charting the data, we used thematic analysis to identify themes in the data. Results: We identified six themes: collaboration/partnerships, power sharing, address the broader context of the patient's life, safe environment, organizational and individual level self-reflection, and training for health-care providers. Conclusion: While it is important to recognize that the provision of culturally safe initiatives depend on the specific interaction between the health-care provider and the patient, having a common understanding of the components of cultural safety, such as those that we identified through this research, will help in the transition of cultural safety from theory into practice.